2013
DOI: 10.1068/b38048
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Methods and Extents of the Usage of Urban Modeling in Urban Design Practice in US Cities

Abstract: Literature suggests that present urban design plans and methods are inadequate to deal with the scale and complexity of contemporary urban form and multidisciplinary collaborative practice. Although recent developments in urban modeling technologies have brought about a wide range of different techniques and potential implementations that may help address this inadequacy, they have not yet made their desired impact on the design process. Failure to use these capabilities extensively in actual practice may resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…The pattern of usage through phases 1-3 shows that the simulation tools have been used at "sometimes", "high", or "very high" extents at all design activities, but they have been used either with little, sometimes or high extents in phase 4 (Figure 2). This pattern is inconsistent with the results of a previous study which showed that IT tools usage was limited at the initial, analytical phase but increased at the conceptual and design production phases (Al-Douri, 2013). They are also inconsistent with the literature which suggests those tools are extensively used at the initial design phase when their influence is potentially the highest and then gradually declines in the following phases.…”
Section: Extent Of Usage Of It Tools At Various Design Phasescontrasting
confidence: 92%
“…The pattern of usage through phases 1-3 shows that the simulation tools have been used at "sometimes", "high", or "very high" extents at all design activities, but they have been used either with little, sometimes or high extents in phase 4 (Figure 2). This pattern is inconsistent with the results of a previous study which showed that IT tools usage was limited at the initial, analytical phase but increased at the conceptual and design production phases (Al-Douri, 2013). They are also inconsistent with the literature which suggests those tools are extensively used at the initial design phase when their influence is potentially the highest and then gradually declines in the following phases.…”
Section: Extent Of Usage Of It Tools At Various Design Phasescontrasting
confidence: 92%
“…But Cities are now considered to be complex organisms with both organisation and interplay of factors seen as more important and challenging than before (Cuthbert, 2008, Al-Douri, 2013. This complexity partly explains the emergence of the concept of the Smart City.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking research suggests that computational tools have not been used for urban design as extensively as they might be (Al-Douri, 2013, Fraser and Bjornsson, 2004, Billger et al, 2017. We could look at this contention from two perspectives: one view could be to say there is a need for more flexible and capable computer programs -ones that allow urban designers to employ different processes in their designs.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated computational urban design methods and tools are thereby seen as important means to help synergize expert knowledge and design integration (Wilson 2018). However, existing planning support systems (PSS) have been criticized to focus too much on technology to sufficiently support planning practice and as being primarily used to inform rather than to support design and decision-making and in consequence of lacking a lasting impact on the design process (Geertman 2006, Batty 2007, Al-Douri 2013. This has mainly been attributed to a lack of transparency and flexibility of the systems, as well as understanding of how they can be applied and best benefit the design process (Vonk et al 2005, Al-Douri 2013.…”
Section: Introductionmentioning
confidence: 99%